Reflexões acerca da “herança” axiológica dos direitos humanos - Vivianny Galvão (Araucaria)
Searching for the fundamentals of any standard means, in other words, seeking to explain its obligation. The theme, in itself, is already complex because it seems to leave to the mercy of each interpreter the choice of the foundations that will justify the duty to fulfill contents so dear to the social life. To justify the recognition of human rights through a line of historical argumentation was the path chosen by important authors, like Norberto Bobbio. The broad scope of work built on the foundations of historical foundations has placed the Declaration of the Rights of Man and the Citizen as the right source of the Universal Declaration of Human Rights. In order to analyze the influence of the French Declaration on the Declaration adopted by the United Nations, there was the debate between Jellinek and Boutmy on the foundations of the French Declaration. It is common to accept that the origin of institutions is directly or indirectly linked to European thought. In the case of the Universal Declaration of Human Rights, it has been found that it is inconsistent to disagree with the idea of necessary grounding between the French Declaration and the aforementioned United Nations resolution. This article presents a brief review of the literature on the fundamentals of human rights and research with qualitative methodology, historical method of procedure.